Protecting the interest of the child in parental child abduction: Malaysian experience - Che Soh @ Yusoff, Roslina (2017)
This paper examines the position of parental child abduction under the Malaysian law and the approach of the courts in dealing with the matter. The paper also examines the ramification of adopting the Hague Convention and related treaties by Malaysia in complying with international standard when dealing with parental abduction and its effect on the long-term interest of the child and to suggest for a more effective solution through which much protection will be provided to children against parental child abduction